(untitled) (European Journal of Pedagogical Initiatives and Educational Practices, 2025)
This article analyzes color-based coloring methods in interior and exterior design. The interaction of the environment, light, materials, and psychological factors play an important role in color selection. Also, color harmony in interior and exterior design, coloring methods based on modern trends and technologies are studied. The article compares classical and innovative approaches and analyzes the impact of color composition on human mood and behavior. The results of this study contain useful recommendations for designers and architects